Pengaruh Power Efek, Komunikasi, Lingkungan Kerja Terhadap Kinerja Karyawan Dalam Perspektif Islam (Studi Pada Badan Pengawas Pemilu Kota Bandar Lampung) - Fatih Fuadi; Diajeng Sekaratu Galuh Aska (CV. ITTC INDONESIA, 2022)
The performance of employees in business companies is required to be effective and efficient so that the business company will develop. One of the indicators of employee performance assessment is absenteeism which can influence factors such as power effects, communication and the work environment. This research is classified as field research, primary data was obtained from questionnaires and interviews while secondary data was obtained through documentation. The method used in this research is a quantitative method using a sample of 18 respondents using a saturated sampling technique. Overall, the results of multiple linear regression analysis and hypothesis testing can be concluded that in this research partially (t test), the power effect has a significant effect on employee performance with a significant value of 0.000 < 0.05 so it can be concluded that Ho is rejected and H1 is accepted, communication has an effect significant at 0.03 < 0.05 so it can be concluded that Ho is rejected and H1 is accepted and the work environment has a significant effect on employee performance with a significant value of 0.001 < 0.05 which can be concluded that Ho is rejected and H1 is accepted. From an Islamic perspective, the performance of Bawaslu employees in the city of Bandar Lampung does not fully fulfill Islamic performance principles based on the principle of trust, some employees are still absent from work, some arrive late.